Novel Dual Acetyl- and Butyrylcholinesterase Inhibitors Based on the Pyridyl-Pyridazine Moiety for the Potential Treatment of Alzheimer's Disease - Mohamed Elsawalhy; Adel A-H; Ebtesam A. Basiony; Salma A. Ellithy; Allam A. Hassan; Eman S. Abou-Amra; Abdelhamid Ismail; Abdulrahman A. Almehizia; Mohamed A. Al-Omar; Ahmed M. Naglah; Nasser A. Hassan (MDPI AG, 2024)
Background: Alzheimer's disease (AD) is characterized by cholinergic dysfunction, making the inhibition of acetylcholinesterase (AChE) and butyrylcholinesterase (BuChE) critical for improving cholinergic neurotransmission. However, the development of effective dual inhibitors remains challenging. Objective: This study aims to synthesize and evaluate novel pyridazine-containing compounds as potential dual inhibitors of AChE and BuChE for AD treatment. Methods: Ten novel pyridazine-containing compounds were synthesized and characterized using IR, 1H NMR, and 13C NMR. The inhibitory activities against AChE and BuChE were assessed in vitro, and pharmacokinetic properties were explored through in silico ADME studies. Molecular dynamics simulations were performed for the most active compound. Results: Compound 5 was the most potent inhibitor, with IC50 values of 0.26 µM for AChE and 0.19 µM for BuChE, outperforming rivastigmine and tacrine, and showing competitive results with donepezil. Docking studies revealed a binding affinity of −10.21 kcal/mol to AChE and −13.84 kcal/mol to BuChE, with stable interactions confirmed by molecular dynamics simulations. In silico ADME studies identified favorable pharmacokinetic properties for compounds 5, 8, and 9, with Compound 5 showing the best activity. Conclusions: Compound 5 demonstrates strong potential as a dual cholinesterase inhibitor for Alzheimer's disease, supported by both in vitro and in silico analyses. These findings provide a basis for further optimization and development of these novel inhibitors.